2015
DOI: 10.1016/j.immuni.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Smad2 and Smad3 Inversely Regulate TGF-β Autoinduction in Clostridium butyricum-Activated Dendritic Cells

Abstract: Colonization with a mixture of Clostridium species has been shown to induce accumulation of induced regulatory T (iTreg) cells in the colon. Transforming growth factor-β (TGF-β) is an essential factor for iTreg cell induction; however, the relationship between Clostridium species and TGF-β remains to be clarified. Here we demonstrated that a gram-positive probiotic bacterial strain, Clostridium butyricum (C. butyricum), promoted iTreg cell generation in the intestine through induction of TGF-β1 from lamina pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
146
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 47 publications
11
146
0
Order By: Relevance
“…In addition, TGFb signaling increases recruitment of the transcription factor PU.1 to the promoter and intronic regions of the Runx3 gene (Chopin et al 2013), which encodes a critical transcription factor in Langerhans cell development (Fainaru et al 2004). It has been proposed that, in the intestinal lamina propria, a combination of TGF-b and bacterial sensing regulates the tolerogenic properties of gut DCs, largely by controlling DC production of TGF-b, which is suggested to direct pTreg-cell generation (Kashiwagi et al 2015). Notably, although autocrine TGF-b signaling confers enhanced TGF-b expression in DCs, the TGF-b-activated Smads appear to play opposing roles in this regulation with Smad3 promoting and Smad2 inhibiting TGF-b production.…”
Section: Regulation Of Immunity By Tgf-bmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, TGFb signaling increases recruitment of the transcription factor PU.1 to the promoter and intronic regions of the Runx3 gene (Chopin et al 2013), which encodes a critical transcription factor in Langerhans cell development (Fainaru et al 2004). It has been proposed that, in the intestinal lamina propria, a combination of TGF-b and bacterial sensing regulates the tolerogenic properties of gut DCs, largely by controlling DC production of TGF-b, which is suggested to direct pTreg-cell generation (Kashiwagi et al 2015). Notably, although autocrine TGF-b signaling confers enhanced TGF-b expression in DCs, the TGF-b-activated Smads appear to play opposing roles in this regulation with Smad3 promoting and Smad2 inhibiting TGF-b production.…”
Section: Regulation Of Immunity By Tgf-bmentioning
confidence: 99%
“…DCs that lack only Smad2 express higher levels of mRNA for TGF-b1 and IL-10, and lower levels of mRNA for inflammatory cytokines, for example, TNF-a, IL-6, and IL-12, and show tolerogenic activity. However, despite the indication that autocrine TGF-b signaling promotes TGF-b production in DCs, whether DCs represent the critical source of TGF-b for pTreg-cell differentiation, as proposed (Kashiwagi et al 2015), remains to be validated by genetic methods, for example, using CD11c-Cre-mediated deletion of floxed Tgfb1. Indeed, it has been shown that T cells themselves are the essential source of TGF-b for Th17 differentiation Gutcher et al 2011).…”
Section: Regulation Of Immunity By Tgf-bmentioning
confidence: 99%
“…1a). Although the mechanism underlying modulation of TGF-b production in the human intestine remains to be elucidated, TGF-b production is upregulated by various factors, such as bacteria, viruses, cytokines, apoptotic cells, and the autocrine/paracrine loop [15,16]. A study using laser-captured micro-dissection reported that TGF-b expression was higher in the lamina propria than the epithelium in a healthy human colon [9].…”
Section: Tgf-b In Ibd Tgf-b Productionmentioning
confidence: 99%
“…Clostridium cluster IV and XIVa were reported to be less abundant in IBD patients than in healthy controls [76]. Another study showed that administration of Clostridium butyricum (cluster I) as a probiotic [77] promoted Treg differentiation through TGF-b1 produced by lamina propria DCs in a TGF-b-Smad and TLR-ERK-AP1 pathway-dependent manner [15].…”
Section: Clostridiummentioning
confidence: 99%
“…Previously, TGFβ signaling was shown to prevent inflammation of the bowel upon activation in the associated dendritic cells 44 . New data shed further light on this process by suggesting that Clostridium species within the microbiota induce TGFβ1 expression in colonic dendritic cells in a model of experimental colitis 45 . This in turn stimulates the generation of immunosuppressive regulatory T (Treg) cells, thereby ameliorating the bowel colitis.…”
Section: Tgfβ Signaling In Immune Regulationmentioning
confidence: 99%